Mechanical and Thermal Properties of Geopolymerized LECA Concrete - Hebah M. Al-Jabali; Abd Al-Kader A. Al Sayed; Mohamed Fahmy; Amr A. Nada; Amr Abdelkhalik (Civil Engineering Journal, 2026)
This study aims to enhance the mechanical and thermal performance of lightweight expanded clay aggregate (LECA) concrete through geopolymerization using iron oxide (Fe₂O₃) and polyethylene glycol 400 (PEG400), combined with surface treatment of LECA aggregates. An experimental program was conducted to evaluate workability, density, water absorption, compressive strength, splitting tensile strength, and bulk electrical resistivity (BER). Various mixtures with different proportions of Fe₂O₃ and PEG400 were prepared with and without aggregate surface treatment. The findings indicate that surface treatment significantly improves the interfacial transition zone, resulting in enhanced overall performance. The optimal mix (treated LECA with 3% PEG400 and 20% Fe₂O₃) achieved a compressive strength of 45 MPa and a splitting tensile strength of 4.0 MPa, representing increases of over 70% compared to the control mix. Additionally, water absorption decreased by 35.6%, while BER increased by 127%, reflecting improved durability and reduced permeability. Workability was also enhanced, with up to a 100% increase in slump without compromising strength. The novelty of this study lies in the synergistic integration of treated LECA, PEG400, and iron oxide within a geopolymer matrix to produce a high-performance, durable, and thermally efficient lightweight concrete. This approach offers a sustainable solution for advanced construction applications.